The production of knowledge in educational policies of the Graduate Programs in Education of the Universidade Estadual Paulista in the period 2009-2013 - Souza, Kellcia Rezende [UNESP]; Micely Kerbauy, Maria Teresa [UNESP] (Unesp-faculdade Ciencias & Letras, 2015)
This study examines the underlying trends research on educational policies in the production of graduate programs in Education of the Universidade Estadual Paulista (UNESP). For this, a literature search was performed with qualitative approach. Data were analyzed from the abstracts content. We take as an object to understand this issue dissertations and theses with theme focused on the area of educational policy. 85 studies were selected, from 2009 to 2013. The works reflect the view of prevailing trends and looks in the field of educational policies of the institution's programs, represented under 5 themes: Studies on government policies and programs; Legislation and the right to education; Financing policies and management; Assessment policies and role of political parties and other civil society organizations. Such analysis shows the progress of the focused field of knowledge and limits are presented for the consolidation of the area.
Keywords: Research; Educational Policy; Graduate School